PENGEMBANGAN VIDEO SEJARAH KOTA JAMBI PERIODE KOLONIAL SEBAGAI MEDIA PEMBELAJARAN SEJARAH LOKAL KELAS XI SMA NEGERI 9 KOTA JAMBI - Yudha Pratama, Singgi; Azmi, Ulul (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2023)
The purpose of this research is to determine the development of Video-Based Learning Media onlearning Local History material at SMA Negeri 9 Jambi City. To see student responses when learningusing Video media. The development model used is ADDIE which consists of 5 stages, namely theAnalysis, Design, Development, Implementation, and Evaluation stages. The subject of this study wasa student of SMA Negeri 9 Jambi City class XI. The feasibility of learning media refers to the resultsof media assessments by experts on the learning media developed. Video-based history learningmedia on Colonial History material in Jambi City that was developed has met the criteria foreligibility / validity for use for grade XI high school students. The results of the media assessment byvalidator I obtained a value of 90.3 with very valid eligibility criteria. The results of the validator IImaterial assessment obtained a value of 87.5 with very valid eligibility criteria. The results of thehistory teacher's assessment on the media aspect obtained a score of 100 with very Good criteria andthe material aspect obtained a value of 97.5 with very Good criteria. The results of the assessment ofstudent responses in the first trial obtained a percentage of 81% with very good eligibil ity criteria,the second trial 90% with very good eligibility criteria, and the third trial obtained a percentage of90.6% with very good eligibility criteria.